Semisynthesis and in Vitro Photodynamic Activity Evaluations of Halogenated and Glycosylated Derivatives of Pheophorbide a. Issue 27 (7th August 2015) - Cieckiewicz, Ewa; Mathieu, Véronique; Angenot, Luc; Gras, Thierry; Dejaegher, Bieke; de Tullio, Pascal; Pirotte, Bernard; Frédérich, Michel
Abstract: The present work focuses on the semisynthesis of halogenated and glycosylated derivatives of pheophorbide a (Ph a ). Because of the low reaction yields enocuntered en route to halogenated derivatives, we then focused only on the semisynthesis of glycosylated derivatives of Ph a with the aim at enhancing the Ph a specificity for cancer cells by introducing β‐galactose moieties expected to bind gal‐1. We applied LC‐SPE‐NMR/MS, to facilitate the direct identification of glycosylated derivatives. The transposition of these analytical methods to a preparative scale facilitated the isolation of glycosylated compounds in quantities sufficient to evaluate in vitro photodynamic efficacies. The in vitro growth inhibitory activity of semisynthesized compounds was then evaluated using the MTT colorimetric assay in the presence and absence of light. However, this pharmacological evaluation method seems to be unable to efficiently yield information about carbohydrate effects in relation to possible compound specificities for gal‐1 overexpressed by B16F10 cancer cells. Abstract : Pheophorbide a (Ph a ) derivatives were semisynthesized to optimize the photodynamic characteristics of the starting compound; halogenation of the 20‐position and glycosylation of the 17c‐position were main goals. Glycosylated compounds were identified by LC‐SPE‐NMR/MS. Photo‐triggered in vitro growth inhibitory activities of all new compounds were evaluated using MTT colorimetric assays.